2015
DOI: 10.1073/pnas.1424175112
|View full text |Cite
|
Sign up to set email alerts
|

T box riboswitches in Actinobacteria: Translational regulation via novel tRNA interactions

Abstract: The T box riboswitch regulates many amino acid-related genes in Gram-positive bacteria. T box riboswitch-mediated gene regulation was shown previously to occur at the level of transcription attenuation via structural rearrangements in the 5′ untranslated (leader) region of the mRNA in response to binding of a specific uncharged tRNA. In this study, a novel group of isoleucyl-tRNA synthetase gene (ileS) T box leader sequences found in organisms of the phylum Actinobacteria was investigated. The Stem I domains o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
77
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(81 citation statements)
references
References 38 publications
4
77
0
Order By: Relevance
“…One example supporting the RNPep world hypothesis is the existence of the T box riboswitch that reflects the expanding function of RNA beyond its sequence when it communicates through structural specificity with its cognate tRNA (Yousef et al, 2003;Saad et al, 2012). Interestingly, the T box riboswitch is a leader RNA that harbors a codon sequence by which it specifically recognizes its cognate tRNA to regulate gene expression through transcription attenuation (Henkin, 2014) and translation initiation inhibition (Sherwood et al, 2015). Therefore, during the RNPep world, one might assume that the T box riboswitch could be a relic of the first RNPep ribozymes capable of aminoacylating bound tRNAs.…”
Section: Ribonucleopeptides At the Origin Of Life?mentioning
confidence: 99%
“…One example supporting the RNPep world hypothesis is the existence of the T box riboswitch that reflects the expanding function of RNA beyond its sequence when it communicates through structural specificity with its cognate tRNA (Yousef et al, 2003;Saad et al, 2012). Interestingly, the T box riboswitch is a leader RNA that harbors a codon sequence by which it specifically recognizes its cognate tRNA to regulate gene expression through transcription attenuation (Henkin, 2014) and translation initiation inhibition (Sherwood et al, 2015). Therefore, during the RNPep world, one might assume that the T box riboswitch could be a relic of the first RNPep ribozymes capable of aminoacylating bound tRNAs.…”
Section: Ribonucleopeptides At the Origin Of Life?mentioning
confidence: 99%
“…Although previous bioinformatics analyses predicted the existence of such a T-box, they were based only on the recognition of the highly conserved T-box bulge sequence (Vitreschak et al 2008;Wels et al 2008;Sherwood et al 2015). In the case of the S. aureus glyS T-box, it was evident that stem I with the exception of the SL GGC codon did not exhibit the same conservation with other characterized T-boxes based on comparison with glyQS T-boxes from B. subtilis, O. iheyensis, and G. kaustophilus that have been structurally characterized (Fig.…”
Section: Identification Of the Glys Leader Sequence And Transcriptionmentioning
confidence: 99%
“…They control transcription of downstream genes that either encode proteins involved in biosynthesis and transport of aa or aminoacyl-tRNA synthetases (aaRSs) which supply ribosomal protein synthesis with the aminoacylated tRNAs (aa-tRNAs) substrates (Henkin 2008(Henkin , 2014. Although their main regulatory mechanism is transcriptional attenuation, recently it was shown that the ileS T-box in Actinobacteria acts via sequestration of the Shine-Dalgarno sequence, thus modulating ribosome binding and translation initiation (Sherwood et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Almost all T-box riboswitches studied to date regulate the expression of the corresponding gene at the level of transcription attenuation, with the exception of a T-box in Actinobacteria recently described, whose target is regulated at the translational level by blocking / deblocking the accessibility of the Shine-Dalgarno (SD) sequence in the mRNA to the ribosome. [7] The T-box mechanism is mostly present in Gram-positive bacteria and, although less common, by comparative genomic analysis it has been identified also in Gram-negative microorganisms. [8,9] Acidithiobacillus ferrooxidans is an acidophilic, Gram-negative, autotrophic, chemolithotrophic, facultative aerobic bacterium that participate in either natural or human-made bioleaching processes.…”
Section: Introductionmentioning
confidence: 99%